2021
DOI: 10.3390/en14165133
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Water-Based Magneto-Hydrodynamic Rotating Nanofluid Flow over a Linear Extending Sheet and Heat Transport Analysis: A Numerical Approach

Abstract: This comparative study inspects the heat transfer characteristics of magnetohydrodynamic (MHD) nanofluid flow. The model employed is a two-phase fluid flow model. Water is utilized as the base fluid, and zinc and titanium oxide (Zn and TiO2) are used as two different types of nanoparticles. The rotation of nanofluid is considered along the z-axis, with velocity  ω*. A similarity transformation is used to transform the leading structure of partial differential equations to ordinary differential equations. By us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Sheriff et al [ 37 ] investigated varying fluid features for water-based nanoparticles for heat and peristaltic propagation. Numerous researchers have utilized nanofluids and hybrid nanofluids to enhance the heat transfer coefficient, including several quality studies [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sheriff et al [ 37 ] investigated varying fluid features for water-based nanoparticles for heat and peristaltic propagation. Numerous researchers have utilized nanofluids and hybrid nanofluids to enhance the heat transfer coefficient, including several quality studies [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arshad et al [ 6 ] discussed the MHD nanofluid movement across an exponentially stretching surface using the Brownian effect. Hussain et al [ 7 ] have explored three-dimensional rotating nanofluid over a stretching surface with a magnetic field for heat transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Madhukesh et al [13] studied hybrid Casson fluid induced by a Riga plate with thermophoretic particle disposition and for heat and mass transportation. Gowda et al [14] have demonstrated Casson-Maxwell fluid through stretchable disks to examine slip flow [15][16][17][18][19]. and Arshad et al [20][21][22] have extensively examined linear and exponential stretching surfaces with external applied effects for nano and hybrid nanofluids.…”
Section: Introductionmentioning
confidence: 99%